Continuity and change in Etruscan domestic architecture - Miller, Paul M. (Access archaeology., 2017)
Etruscan architecture underwent various changes between the later Iron Age and the Archaic period. This book reconsiders these changes by focusing on the building materials and techniques used in the construction of domestic structures.